Metallic Transition‐Metal Chalcogenides: Electrically Robust Single‐Crystalline WTe(2) Nanobelts for Nanoscale Electrical Interconnects (Adv. Sci. 3/2019) - Song, Seunguk (Adv Sci (Weinh), 2019)
In article number 1801370, Soon‐Yong Kwon and co‐workers investigate single‐crystalline WTe2 nanobelts from a eutectic metal alloy, which can be a prominent interconnect candidate because of their superior electrical performance and robustness. The successful choice of new interconnect materials from the current 2D library will drive improvements to existing process technologies and will exploit the potential of the assembly of 2D atomic crystals into atomic crystal‐based systems and circuits. [Image: see text]